More ideas for science projects - Gardner, Robert, 1929- (New York : F. Watts, 1989)
Presents ideas for an exploration of how to set up science projects in the areas of astronomy, ecology, energy, biology, anatomy, botany, physics, and engineering.
Includes index.
Bibliography: p. 137-141.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
7.3
Keywords: Science projects -- Juvenile literature; Science projects; Science -- Experiments